Serum Concentrations of Betatrophin and Its Association with Indirect Indices of Insulin Resistance and Beta Cell Function in Women with Polycystic Ovary Syndrome - Agnieszka Adamska; Agnieszka Łebkowska; Małgorzata Jacewicz; Anna Krentowska; Justyna Hryniewicka; Sławomir Wołczyński; Maria Górska; Irina Kowalska (International Journal of Endocrinology)
Introduction. Data underline the role of betatrophin in glucose homeostasis. Polycystic ovary syndrome (PCOS) is characterized by insulin resistance (IR). The aim of our study was to investigate the relationship of serum betatrophin concentrations with indirect indices of IR and insulin secretion in women with PCOS, compared to the control group. Methods. The study group comprised 43 women with PCOS and 16 controls. IR was assessed by HOMA-IR and Matsuda index. Insulin secretion was evaluated with HOMA-B. An oral glucose tolerance test (OGTT) with estimation of serum betatrophin concentrations was performed. Results. Glucose load resulted in an increase in serum betatrophin concentrations in the control group (p=0.02). Serum betatrophin concentrations at 120 min of OGTT were lower in women with PCOS than in the control group (p=0.02). We observed positive correlations between baseline serum betatrophin concentrations and HOMA-IR (r=0.39, p=0.008), negative correlations with Matsuda index (r=−0.31, p=0.004), and a positive relationship with HOMA-B (r=0.38, p=0.01) in women with PCOS. Multiple regression analysis revealed that HOMA-B (β=0.47, p=0.001) was an independent factor connected to serum betatrophin levels in PCOS. Conclusions. Serum concentrations of betatrophin are connected with insulin resistance and beta cell function and did not change after glucose load in women with PCOS.